Clinical performance of a new post system: I post - Tanushree Sancheti; Lalitagauri Mandke (Wolters Kluwer Medknow Publications, 2016)
One of the important stages in endodontic therapy is to restore the tooth with a stable restoration for mastication and aesthetic purposes. Posts have been used effectively and successfully for postendodontic restorations. This case report presents the use of a new post system - I post, a prefabricated metal post with a unique design. Two posterior teeth were restored postendodontically with the I post, with a follow-up of 3 months. The teeth were asymptomatic, and radiographic evidence showed that the posts were in position with no evidence of fracture or coronal leakage. This new post system will go a long way in providing the clinician with a predictable and efficient prosthesis foundation.